2013
DOI: 10.1371/journal.pone.0083535
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Pattern of the FAE1 Gene in Brassicaceae and Its Correlation with the Erucic Acid Trait

Abstract: The fatty acid elongase 1 (FAE1) gene catalyzes the initial condensation step in the elongation pathway of VLCFA (very long chain fatty acid) biosynthesis and is thus a key gene in erucic acid biosynthesis. Based on a worldwide collection of 62 accessions representing 14 tribes, 31 genera, 51 species, 4 subspecies and 7 varieties, we conducted a phylogenetic reconstruction and correlation analysis between genetic variations in the FAE1 gene and the erucic acid trait, attempting to gain insight into the evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
(74 reference statements)
3
20
0
Order By: Relevance
“…A FAE1 gene phylogeny of Brassicaceae suggested that purifying selection is the major evolutionary force acting on the gene which is consistent with similar findings in another fatty acid elongase gene EVOVL5 responsible for encoding an enzyme involved in the biosynthesis of long-chain PUFAs in fishes [39]. This suggests that since FAE1 is involved in TAG biosynthesis; focus on the sequence variation and phylogeny of genes responsible for seed oil content will be useful in understanding the evolutionary pattern of these genes in Angiosperms.…”
Section: Discussionsupporting
confidence: 72%
“…A FAE1 gene phylogeny of Brassicaceae suggested that purifying selection is the major evolutionary force acting on the gene which is consistent with similar findings in another fatty acid elongase gene EVOVL5 responsible for encoding an enzyme involved in the biosynthesis of long-chain PUFAs in fishes [39]. This suggests that since FAE1 is involved in TAG biosynthesis; focus on the sequence variation and phylogeny of genes responsible for seed oil content will be useful in understanding the evolutionary pattern of these genes in Angiosperms.…”
Section: Discussionsupporting
confidence: 72%
“…This result further strengthen the hypothesis that, although the FAE1 enzymes are highly conserved in the plant kingdom and independently of the acyl-CoA pools, certain amino acid residues or protein domains, not directly related with the active site, could be behind the high erucic acid trait phenotype of certain plants, particularly those from the Brassicaceae family. Recent studies, suggested a correlation between several sequence motifs and the content of erucic acid in seeds (Sun et al 2013). A search of the seven motifs identified by Sun et al (2013) as associated with high erucic acid accumulation in seeds showed that all of them were present in the TaFAE1 sequences from both Pennycress lines while none of them were detected in the AtFAE1 sequence (Fig.…”
Section: Characterization Of the Tafae1 Gene From Nasc And French Penmentioning
confidence: 89%
“…Recent studies, suggested a correlation between several sequence motifs and the content of erucic acid in seeds (Sun et al 2013). A search of the seven motifs identified by Sun et al (2013) as associated with high erucic acid accumulation in seeds showed that all of them were present in the TaFAE1 sequences from both Pennycress lines while none of them were detected in the AtFAE1 sequence (Fig. 5).…”
Section: Characterization Of the Tafae1 Gene From Nasc And French Penmentioning
confidence: 89%
“…However, the occurrence of high SOC (>27%) proportions in four tribes: Cardamineae, Thlaspideae, Brassiceae, and Camelineae (Table , Fig. 4) suggests that examining the phylogenies from genes regulating seed oil traits will help understand the underlying mechanism of the observed pattern (Sun et al, ). A phylogeny of Brassicaceae generated from the FAE1 gene suggested that purifying selection is the major evolutionary force acting on the gene, which is consistent with similar findings in another fatty acid elongase gene— EVOVL5 —responsible for encoding an enzyme involved in the biosynthesis of long‐chain PUFAs in fish (Carmona‐Antoñanzas et al., ).…”
Section: Discussionmentioning
confidence: 99%